Perceived performances of peer learning and education approach on malaria prevention through primary schools communities in rural Ethiopia: Peer educators' perspectives - Deressa, Alemayehu; Eyeberu, Addis; Gamachu, Mulugeta; Debella, Adera; Abamecha Ababulgu, Fira (Frontiers in Public Health, 2022)
Background Schools are viewed as natural hubs and an effective strategy for promoting community healthy practices such as malaria prevention and control. This study examined the perceived performance of the peer learning and education approach to malaria prevention in rural primary school communities in Ethiopia, which has thus far received little attention. Methods Post-intervention data were collected from 404 randomly selected peer educators between 2 April and June 2020 using a structured questionnaire. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 24.0. Multiple linear regression was used to identify independent predictors of perceived performance of school-based peer learning and educational approach. A statistically significant p-value of < 0.05 was considered statistically significant. Results Four hundred and one educators (99.2%) completed the interview. The mean score of perceived performance was 44.31 (SD = 6.13) which was above the expected mean level range of 11–55. Feasibility (β = 0.253, 95% CI = [0.313, 0.682]), and appropriateness (β = 0.163, 95% CI = [0.099, 0.442]) were significantly associated with perceived performance. Self-efficacy, malaria risk perception, eagerness to share and learn from each other's experiences, and preference for more than one subject were all significantly associated with perceived performance, with (β = 0.097, CI = [0.017, 0.242]), (β = 0.143, CI = [0.071, 0.233]), (β = 0.207, CI = [0.308, 0.826]) and (β = 0.075, CI = [0.084, 2.511]) at 95% CI, respectively. Conclusions The peer learning and education approach to malaria prevention and control in schools has a noticeably high level of perceived performance. Thus, it is recommended that when designing and implementing such programs through schools, personal and social (team) factors such as self-efficacy, risk perceptions, and peer education team spirit be considered.